Physics and Engineering Design of a Low-Aspect-Ratio Quasi-Axisymmetric Stellarator CHS-qa - Okamura, S., author; Matsuoka, K., author; Nishimura, S., author; Isobe, M., author; Nomura, I., author; Suzuki, C., author; Shimizu, A., author; Murakami, S., author; Nakajima, N., author; Yokoyama, M., author; Fujisawa, A., author; Ida, K., author; et al. (Toki, Japan : NIFS, 2000)
PSZJBL